2021
DOI: 10.21873/invivo.12451
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Capecitabine Corneal Side Effects With Autologous Blood-derived Serum Eye Drops

Abstract: Background/Aim: To describe the clinical progress and management of ocular side effects in a 35-yearold patient with metastatic breast cancer who underwent oral chemotherapy with capecitabine and lapatinib. Materials and Methods: Slit lamp evaluation revealed bilateral perikeratic hyperemia, perilimbal conjunctival edema associated with corneal marginal infiltrates and epithelial and anterior stromal defects in both eyes. Slit lamp examination, in vivo confocal microscopy and anteriorsegment optical coherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…19,20 Reversibility of severe contact lens- induced LSCD and improvement of BCVA with the 2-month use of 20% AS treatment was reported by Yeh et al 14 A recent report by Di Staso F et al showed that 30% AS could reverse corneal toxicity resembling LSCD from capecitabine. 21 It is unclear whether the mechanism with which chronic contact lens use leads to LSCD is similar to that of LSCD in glaucoma surgery patients. This underlines the need to further assess how potentially alternative routes of acquiring LSCD affect the efficacy of AS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Reversibility of severe contact lens- induced LSCD and improvement of BCVA with the 2-month use of 20% AS treatment was reported by Yeh et al 14 A recent report by Di Staso F et al showed that 30% AS could reverse corneal toxicity resembling LSCD from capecitabine. 21 It is unclear whether the mechanism with which chronic contact lens use leads to LSCD is similar to that of LSCD in glaucoma surgery patients. This underlines the need to further assess how potentially alternative routes of acquiring LSCD affect the efficacy of AS treatment.…”
Section: Discussionmentioning
confidence: 99%